Knowledge, attitudes, and practices toward training of vascular access in chronic hemodialysis patients among nephrology fellows in Southwest China - Yaling Zhang; Qiang He; Xingyu Chen; Hao Huang; Ming Li (Scientific Reports)
Abstract This cross-sectional study examined the knowledge, attitudes, and practice (KAP) of training of vascular access in chronic hemodialysis patients among nephrology fellows in Southwest China. Nephrology fellows in Southwest China were recruited from June 1st to 10th, 2024. The demographic characteristics and KAP scores were determined using a self-designed questionnaire. Finally, 210 valid questionnaires were included. Among the participants, 37.6% were 36–40 years old, and 54.3% were females. The median knowledge, attitude, and practice scores were 19 (IQR: 17–20) (possible maximum of 20), 36 (IQR: 35–37) (possible maximum of 50), and 46 (IQR: 38–60) (possible maximum of 80), respectively. Knowledge and attitudes were correlated (Pearson’s r = 0.439, P < 0.001), as well as knowledge and practice (r = 0.645, P < 0.001) and attitudes and practice (r = 0.560, P < 0.001). Mediation analysis showed that the knowledge scores (β = 0.266, P < 0.001), attitude scores (β = 0.268, P < 0.001), gender (β=-0.149, P = 0.001), nephrology experience (β = 0.135, P = 0.005), and experience of leading a vascular access-related surgery or procedure (β=-0.374, P < 0.001) had direct influences on practice, while the knowledge scores (β = 0.130, P < 0.001), professional background (β=-0.186, P < 0.001), and experience of leading a vascular access-related surgery or procedure (β=-0.070, P = 0.006) had indirect influences on practice. The study indicated that nephrology fellows in Southwest China had good vascular access knowledge but moderate attitudes and practices. Specific areas would require training to improve the practice of vascular access for patients requiring maintenance hemodialysis.